Responsibility for Future Genenerations – Scope and Limits - Birnbacher, Dietrich (Studia Ecologiae et Bioethicae, 2009)
Abstract is not available. This paper is published both in English and in Polish. Attached file consists of original English version, and then Polish translation (from page 90).